The politics of mourning in post-communist Romania: unravelling the thanatopolitics of grievable deaths. - Rusu, Mihai Stelian (Mortality, 2020)
National days of mourning are state-sponsored rituals of collective grief enacted in the public sphere by political authorities to symbolically mark and emotionally cope with a socially significant loss. These officially declared and ceremonially performed state rituals of communion in grief provide privileged epistemic opportunities for unravelling the politics of grievability underpinning a society's willingness to mourn its dead. This paper focuses on comparing and contrasting two case studies – the Colectiv nightclub fire and the flu epidemics – in order to grasp the politics of national mourning in the Romanian post-communist context. After identifying the criteria of grievability underlying the declaration of national mourning in cases of mass death as consisting in a 'chronotopic togetherness' in death that is characterised by an 'instantaneity of emotional shock,' the paper argues for enlarging these criteria of grievability so as to include the victims of socially invisible traumas inflicted by structural violence, such as those killed in epidemics and car road accidents.